2021
DOI: 10.3389/fmicb.2021.714233
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces tardus sp. nov.: A Slow-Growing Actinobacterium Producing Candicidin, Isolated From Sediments of the Trondheim Fjord

Abstract: Marine environments are home to an extensive number of microorganisms, many of which remain unexplored for taxonomic novelty and functional capabilities. In this study, a slow-growing Streptomyces strain expressing unique genomic and phenotypic characteristics, P38-E01T, was described using a polyphasic taxonomic approach. This strain is part of a collection of over 8,000 marine Actinobacteria isolates collected in the Trondheim fjord of Norway by SINTEF Industry (Trondheim, Norway) and the Norwegian Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The microbial concentration in the product is directly related to proper colonization and efficacy since the number of viable cells disposed of in the crop needs to be enough to promote the nutrition and protection of the plant (227). One of the main challenges faced in developing actinomycete-based products is to achieve high culture concentrations at large-scale production, once they show a slower reproduction rate than other bacteria (228,229). In addition, liquid cultures of actinomycetes tend to form aggregates and mycelial pellets, making homogenization difficult (230).…”
Section: Actinomycetes Application In Crops: Methods and Challengesmentioning
confidence: 99%
“…The microbial concentration in the product is directly related to proper colonization and efficacy since the number of viable cells disposed of in the crop needs to be enough to promote the nutrition and protection of the plant (227). One of the main challenges faced in developing actinomycete-based products is to achieve high culture concentrations at large-scale production, once they show a slower reproduction rate than other bacteria (228,229). In addition, liquid cultures of actinomycetes tend to form aggregates and mycelial pellets, making homogenization difficult (230).…”
Section: Actinomycetes Application In Crops: Methods and Challengesmentioning
confidence: 99%
“…The fatty acid profile of the strains is in agreement with reported Streptomyces species; for instance S. colonosanans MUSC 93J T , S. tardus P38-E01 T , S. spinosus SBTS01 T and S. shenzhenensis subsp. oryzicola W18L9 T , which contain anteiso-C 15:0 (21.3–26.6%) and iso-C 16:0 (15.1–30.0%) as major fatty acids ( Law et al, 2017 ; Králová et al, 2021 ; Kaewkla et al, 2022 ). The whole-cell sugars of G1–G3 were glucose and ribose ( Supplementary Figures S2A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acids profiles of G1-G3 are presented in Table 2. The major cellular fatty acids (percentage greater than 10%) in G1 and G2 were anteiso-C 15:0 (25.83 and 25.12%, respectively), iso-C 16:0 (18.28 and 15.90%) and C 16:0 (14.14 and 14.34%); ) and iso-C 16:0 (15.1-30.0%) as major fatty acids (Law et al, 2017;Králová et al, 2021;Kaewkla et al, 2022). The whole-cell sugars of G1-G3 were glucose and ribose (Supplementary Figures S2A-C).…”
Section: Chemotaxonomic Analysesmentioning
confidence: 99%
“…However, when we consider the factor of plant exudates, we might explain this contradicting results by the differential response of the genus due to the exposure to different exudates of two different plants, e.g., Brassica napus in prior research ( Jiménez-Gómez et al, 2019 ), while Moringa oleifera in the present study . Another recent report indicated that a member of genus Streptomyces harbors 186 CAZyme domain sequences, where families of the CAZy class GH are the most abundant followed by those of GT ( Králová et al, 2021 ). This makes the rhizosphere microbiome of Moringa oleifera a good source of these economically-important enzymes.…”
Section: Discussionmentioning
confidence: 99%